Echocardiography Screening for Diagnosis of Latent RHD Using Nurses: Is the Project Feasible for Nepal? - Regmi, Prakash Raj; Kafle, Riju (Nepalese Heart Journal, 2021)
Rheumatic Heart Disease (RHD) is a preventable disease which occurs years or decades after the onset of Acute Rheumatic Fever (ARF) in childhood. The prevalence of RHD is still high in Nepal, with most cases of latent RHD concentrated in the rural, resource-limited setting. The sequelae of latent RHD cases often manifest decades later, causing a significant burden on the health system. Training of non-experts with simple protocols in such remote setting for screening of latent RHD is showing promising results worldwide. Screening of latent RHD is advocated in RHD endemic areas where early detection by echo screening can alleviate a massive burden on morbidity and mortality in the future. More research is needed to explore this possibility in the context of an endemic country like Nepal to tackle the burden of RHD.